Migration and the 'children of the transition': unravelling the experiences of young, highly skilled Bulgarians in the UK - Genova, Elena Stoyanova (2017)
After years of European integration, Favell’s (2008a) ‘Eurostars’ have been joined by many, who perceive the freedom of movement as a right, rather than a privilege. The first and second wave of Eastern enlargement of the EU in 2004 and 2007 have thus changed the outlook of the European migratory regime, placing East-West migratory flows firmly at the centre of both public and academic immigration debates across Europe. This thesis aims to contribute to the growing literature on Central and Eastern European migration to the West by focusing on a relatively understudied group of people – young, highly skilled Bulgarians in the UK. Adopting a broad definition of the term ‘highly skilled’, the study focuses on university students and young professionals. The thesis draws on multi-sited ethnographic research with 37 young Bulgarians, born shortly before or after the democratic changes in 1989. Often referred to as ‘the children of the transition’, this group of people belongs to the first post-accession migratory flows from Bulgaria. By scrutinising young, highly skilled Bulgarians’ experiences of living, working and/or studying in the UK, the study focuses on what happens before, during and as a result of migration. More specifically, the thesis explores three interrelated aspects of the participants’ migratory experiences. Firstly, it analyses young Bulgarians’ pre-migratory context and the macro, meso and micro factors that underpin their decisions to choose Britain as a destination. Secondly, it looks at how they adjust to the host society and how they respond to processes of othering. The emotion-led approach focuses on the costs and benefits of migration as well as on the variety of everyday, counterbalancing strategies employed by young, highly skilled Bulgarians. Finally, the study scrutinises the implications that migration as a life event has upon their identities and plans for the future. Ultimately, the thesis argues that the tension created between migration as a project and as a reality unlocks a period of liminality, which impacts upon migrants’ identities and plans for the future. The exploration of the latter reveals the strong prominence of narratives of success with varying conceptualisations of return.